2017
DOI: 10.3389/fpsyt.2017.00036
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Styles and Suicide-Related Behaviors in Adolescence: The Mediating Role of Self-Criticism and Dependency

Abstract: Insecure attachment and the personality dimensions of self-criticism and dependency have been proposed as risk factors for suicide in adolescents. The present study examines whether self-criticism and dependency mediate the relationship between insecure attachment styles and suicidality. A sample of 340 high-school students (73.2% females), ranging in age from 13 to 20 years (M = 16.47, SD = 1.52), completed the Depressive Experiences Questionnaire for Adolescents, the Depressive Experiences Questionnaire for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 79 publications
1
34
1
4
Order By: Relevance
“…Individuals in our sample who were rated as having higher levels of anaclitic traits appeared to be at higher risk for chronic suicidal behavior, but only when their internal representations were hostile, unintegrated, and imbued with malevolent relational expectations. Whereas prior studies identified connections between high interpersonal dependency-a feature that is often, although not always, associated with borderline personality disorder (Levy, Edell, & McGlashan, 2007)-and suicide (Campos, Besser, & Blatt, 2012;Campos et al, 2018;Falgares et al, 2017;Sobrinho et al, 2016), the current results highlight the importance of an impaired capacity to carry generally benign versus malevolent views of interpersonal relationships and sense of self in the prediction of who may be of greatest risk for chronic suicidality. Indeed, in the current sample, high anaclitic traits were actually associated with lower rates of suicide attempts in individuals who demonstrated an understanding of self and others that was characterized by relatively positive expectations for interpersonal outcomes.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Individuals in our sample who were rated as having higher levels of anaclitic traits appeared to be at higher risk for chronic suicidal behavior, but only when their internal representations were hostile, unintegrated, and imbued with malevolent relational expectations. Whereas prior studies identified connections between high interpersonal dependency-a feature that is often, although not always, associated with borderline personality disorder (Levy, Edell, & McGlashan, 2007)-and suicide (Campos, Besser, & Blatt, 2012;Campos et al, 2018;Falgares et al, 2017;Sobrinho et al, 2016), the current results highlight the importance of an impaired capacity to carry generally benign versus malevolent views of interpersonal relationships and sense of self in the prediction of who may be of greatest risk for chronic suicidality. Indeed, in the current sample, high anaclitic traits were actually associated with lower rates of suicide attempts in individuals who demonstrated an understanding of self and others that was characterized by relatively positive expectations for interpersonal outcomes.…”
Section: Discussioncontrasting
confidence: 86%
“…In several studies, self-criticism was related to suicidality mainly through indirect associations with depression (Sobrinho et al, 2016), perceived parental criticism (Baetens et al, 2015;Campos et al, 2013), and distress (Campos et al, 2018), or in some cases actually related to lower rates of suicidality (Rost, Luyten, & Fonagy, 2018). In contrast, anaclitic personality traits (also often referred to as high dependency) have been found to relate to suicide through an association with attachment anxiety (Falgares et al, 2017), or when combined with high self-criticism and distress (Campos et al, 2018;Sobrinho et al, 2016).…”
mentioning
confidence: 99%
“…As expected, perceptions of negative interactions with parents in the first 16 years of life were associated with higher levels of suicidal ideation, consistent with previous research findings (e.g., Donath et al, ; Heider et al, ; Saffer et al, ). Anxious and avoidant dimensions of attachment were also correlated with suicidal thinking as suggested by other studies (e.g., Aaltonen et al, ; Falgares et al, ; Park et al, ). Although Nunes and Mota () suggested that attachment would be the main mediator of the relationship between parenting and suicidal ideation, we understand that suicidal ideation formation involves the core psychological states of defeat and entrapment as proposed by the IMV model and supported by previous studies (e.g., Dhingra et al, , ; Owen et al, ; Wetherall et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…La visión negativa de uno mismo sería el factor predictivo más fiable de la aparición de sintomatología (McLewin & Muller, 2006). En estudios previos se ha observado que la alta asociación entre el apego temeroso y psicopatología viene dada por la alta visión negativa de sí mismo y de los demás (Camps et al, 2014;Falgares et al, 2017) Otro punto a destacar es el gran porcentaje de adolescentes participantes que presentó apego de tipo inseguro, lo que difiere de las investigaciones en el contexto internacional, en las que se ha encontrado una mayor proporción de apego seguro en muestras no clínicas de adolescentes (Muris, Meesters, van Melick, & Zwambag, 2001). Sin embargo, los hallazgos de la presente investigación son consistentes con el estudio chileno de Spencer, Guzmán, Fresno y Ramos (2013) realizado con jóvenes y adultos jóvenes del sur de Chile.…”
Section: Discussionunclassified